2017
DOI: 10.1515/johr-2017-0014
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Lasiodiplodia theobromae Causing Needle Blight and Stem Canker Diseases on Araucaria heterophylla in Ethiopia

Abstract: Canker and needle blight of Araucaria heterophylla (Norfolk Island pine) trees were observed during the surveys conducted in Addis Ababa and Adama cities (Ethiopia) from November to December 2016. The main objective of this study was to investigate fungal pathogens that cause diseases on Araucaria heterophylla trees. Six localities with Araucaria heterophylla plantings were purposively surveyed for disease symptoms. Samples from symptomatic parts of trees were collected, surface sterilized, cultured on PDA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…Although it is known for its ability to withstand severe conditions, diseases are major factors that affect the health of royal poinciana [3,4]. Many of the phytopathogens can cause diseases on host plants, including royal poinciana [5][6][7][8]. Therefore, careful attention should be attained to the causal agent of stem canker disease on royal poinciana, taking into account the frequency of disease incidence, the geographical distribution and the environmental conditions favorable to the disease occurrence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although it is known for its ability to withstand severe conditions, diseases are major factors that affect the health of royal poinciana [3,4]. Many of the phytopathogens can cause diseases on host plants, including royal poinciana [5][6][7][8]. Therefore, careful attention should be attained to the causal agent of stem canker disease on royal poinciana, taking into account the frequency of disease incidence, the geographical distribution and the environmental conditions favorable to the disease occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…In general, we noticed dieback, canker and gummosis, which ultimately led to complete dryness and death of royal poinciana trees (Figure 1). Although some studies have reported several fungi to cause cankers on plant species [5][6][7][8], others have recorded N. dimidiatum on almond, dragon fruit, eucalyptus, fig and plum, displaying disease symptoms of canker and dieback in different places of the world [13][14][15]28]. In general, environmental stress has negative impact on the severity of disease, depending on the level and duration of the stress, and the sensitivity and developmental stage of the plant species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This fungus is an oftenencountered endophyte and an opportunistic pathogen causing disease when its host is in unfavorable condition. L. theobromae can live in more than 500 species of tropical and subtropical plants (Darge 2017). L. theobromae isolated from the Piper hispidum Sw plant has antibacterial activity against some bacteria species (Orlandelli et al 2012).…”
Section: Identity Of Endophytic Fungi Producing Anti-staphylococcus Amentioning
confidence: 99%